PENGARUH SERTIFIKASI GURU TERHADAP KINERJA GURU MATA PELAJARAN EKONOMI DI SMA NEGERI SE-KECAMATAN KOTA BARU KOTA JAMBI - Redi Indra Yudha, Fransiskus Nugroho, (SJEE (Scientific Journals of Economic Education), 2018)
This study aims to determine the description of respondents and the influence of teacher certification on the performance of economics subject teachers in SMA Negeri Se-Kecamatan Kota Baru. Based on the data analysis on the results of research that there is a significant influence between teacher certification on the performance of economics subject teachers in SMA Negeri Se-Kecamatan Kota Baru. With result of model summary R = 0,059 and R Square = 0,003. Because α (Sig) <0.05, then regression can be used to predict teacher certification at 95% confidence level. In the coefficient B constant value = 54,573, states that if teacher certification variables are ignored, then teacher performance = 54,573. Meanwhile, the variable value for certification (X) is 0.760, stating that if the teacher certification level is included, then teacher performance increases around 0.760. Keyword : Teacher Sertification, Teacher Performance.